2001
DOI: 10.1379/1466-1268(2001)006<0153:efhaab>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for Hsp70 as a biomarker of effect of pollutants on the earthworm Lumbricus terrestris

Abstract: Induction of heat shock proteins (Hsps) is often associated with a cellular response to a harmful stress or to adverse life conditions. The main aims of the present study were (1) to assess if stress-induced Hsp70 could be used to monitor exposure of the earthworm species Lumbricus terrestris to various soil pollutants, (2) to assess the specificity of pollutants in their tissue targeting and in Hsp70 induction, and (3) to evaluate if dose-response relationships could be established and if the stress-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 42 publications
4
64
2
Order By: Relevance
“…FcHsp70 can be induced by copper exposure at transcription level in Chinese shrimp F. chinensis. It has been reported that Hsp70 could be responsive to a wide spectrum of heavy metal pollutants such as Pb, Hg, Ag, Co, or Ni at either the protein or the mRNA levels (Murata et al 1999;Nadeau et al 2001). Studies in aquatic invertebrates have shown that heat shock proteins contribute significantly to both organism adaptation to the environments and to survival under acute environmental stresses (Sanders 1993).…”
Section: Discussionmentioning
confidence: 99%
“…FcHsp70 can be induced by copper exposure at transcription level in Chinese shrimp F. chinensis. It has been reported that Hsp70 could be responsive to a wide spectrum of heavy metal pollutants such as Pb, Hg, Ag, Co, or Ni at either the protein or the mRNA levels (Murata et al 1999;Nadeau et al 2001). Studies in aquatic invertebrates have shown that heat shock proteins contribute significantly to both organism adaptation to the environments and to survival under acute environmental stresses (Sanders 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in recent years have correlated the expression of hsp70 with known toxicological endpoints [51][52][53]. The efficiency of hsp70 expression as biomarker of environmental pollution has been advocated by many researchers [36,51,[54][55][56][57][58][59]. Recently a number of studies have been made to include more and more environmental pollutants to validate the above hypothesis.…”
Section: Hsp70 In Environmental Monitoringmentioning
confidence: 99%
“…Potentially, combinations of heavy metals can induce such distinctive patterns of Hsp expression in soil nematodes that these patterns can become diagnostic fingerprints for specific toxicants in soil [62]. Additional examples of Hsp70 expression in environmental monitoring concern rotifers [63], fish [59,[64][65][66][67], mollusks [39,40,[68][69][70][71][72], algae [73], and earthworm [57].…”
Section: Hsp70 In Environmental Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of hsps within the cellular stress response and their ability to integrate overall adverse effects on protein integrity also make them informative biomarkers for tracking environmental pollution (Sanders 1990;De Pomerai 1996;Kammenga et al 2000;Nadeau et al 2001). Among the numerous classes of stress proteins, the stress-70 (hsp70) family is in this respect far best investigated.…”
Section: Introductionmentioning
confidence: 99%